EXHAUST TEMPERATURE ANALYSIS OF UAV PROPELLER MATERIALS - Suherman Mukti; Fadli Cahya Megawanto; Hari Arthaa (Majalah Ilmiah Pengkajian Industri, 2020)
This paper presents an exhaust temperature analysis of a UAV Propeller Material to maintain the performance of the propulsion system during operation, especially in a long-range condition. A pusher Propeller experiences direct contact with heat from the exhaust gas. In this study, a Beechwood material with a protective layer of corrosion prevention is used as a propeller blade that works at a range of high temperatures. An experimental methodology was carried out to analyse the strength and propeller deformation. The results of this experimental study show that conservatively the propeller will be heated to 32.9°C. Since this is below the temperature limit, the exhaust gas to pusher propeller on UAV does not affect the propeller performance.Key Words: Exhaust; Temperature; UAV; Propeller; Wood